Examiners' and Candidates' Perspectives on the First Performance-Based Assessment of the Saudi National Anesthesiology Board Final Exam - Abdulaziz M. Boker, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The Saudi Board of Anesthesia introduced a performance-based, objective, structured, clinical examination to supplement key and missing components in the traditional fi nal board exam. This study aims to describe briefl y the development, implementation and evaluation of the fi rst high stake Saudi Board of Anesthesia exam after incorporation of objective, structured, clinical examination according to the participants’ perspectives. After implementation of performance-based exams for the fi rst time, a questionnaire was distributed to the candidates and examiners to explore their perception of the exam. Twenty-three candidates and 20 examiners participated in the Saudi Board exam for anesthesia residency held on November 2015. The candidates as well as the examiners were very satisfi ed with the explanation of the exam process before the exam taking, the time allotted for the active stations as well as the organization and fairness of the exam with no significant difference between males and females. In conclusion, the objective, structured, clinical examination is well perceived by the examinees as a fair and acceptable assessment tool in the fi nal exam of the Saudi Board of Anesthesia. We conclude that objective, structured, clinical examination is recommended to be used by other Saudi high stake exams.